(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In this article the issues of organizing practical solutions to methodological problems of modern historiography in Uzbekistan are analyzed. Current issues in the conduct of historical research have been identified on the basis of evidence, and specific solutions have been given to these problems. Solutions have been given to the most important issues that historians in Uzbekistan should pay attention to in covering historical processes. Although there have been many achievements in the field of historiography since independence, the existence of unresolved problems has been shown as a scientific novelty.